Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1093/mnras/stx320
|View full text |Cite
|
Sign up to set email alerts
|

Four new massive pulsating white dwarfs including an ultramassive DAV

Abstract: We report the discovery of four massive (M > 0.8 M ) ZZ Ceti white dwarfs, including an ultramassive 1.16 M star. We obtained ground based, time-series photometry for thirteen white dwarfs from the Sloan Digital Sky Survey Data Release 7 and Data Release 10 whose atmospheric parameters place them within the ZZ Ceti instability strip. We detect mono-periodic pulsations in three of our targets (J1053, J1554, and J2038) and identify three periods of pulsation in J0840 (173, 327, and 797 s). Fourier analysis of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 59 publications
(81 reference statements)
0
44
0
5
Order By: Relevance
“…4, top) obtained with the Thai National Telescope (TNT) -two nights in January and two in February 2019 -unambiguously confirmed the variability as a single pulsation mode. The 840 s period is found to be typical for hydrogen-atmosphere white dwarfs with these stellar parameters 24 . While a single peak in the Fourier transform ( Fig.…”
mentioning
confidence: 84%
“…4, top) obtained with the Thai National Telescope (TNT) -two nights in January and two in February 2019 -unambiguously confirmed the variability as a single pulsation mode. The 840 s period is found to be typical for hydrogen-atmosphere white dwarfs with these stellar parameters 24 . While a single peak in the Fourier transform ( Fig.…”
mentioning
confidence: 84%
“…Besides their high magnetic fields, most of them have been shown to be massive, and responsible for the high-mass peak at 1 M of the WD mass distribution; for instance: REJ 0317-853 has M ≈ 1.35 M and B ≈ (1.7-6.6) × 10 8 G ( Barstow et al 1995;Külebi et al 2010); PG 1658+441 has M ≈ 1.31 M and B ≈ 2.3 × 10 6 G (Liebert et al 1983;Schmidt et al 1992); and PG 1031+234 has the highest magnetic field B ≈ 10 9 G (Schmidt et al 1986;Külebi et al 2009). The existence of ultra-massive WDs has been revealed in several studies (see e.g., Castanheira et al 2013;Hermes et al 2013;Curd et al 2017;Camisassa et al 2019;Gentile Fusillo et al 2018;Jiménez-Esteban et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This ultra-massive ZZ Ceti star was discovered by Curd et al (2017) Our best fit model is characterized by χ 2 = 0.14, δ = 0.37 s, σ = 0.38 s, and BIC= −0.37 with one period (797.4 s) identified as a ℓ = 2 mode, and the remaining periods identified as ℓ = 1 modes. The derivation of the stellar parameters gives T eff = 12 550 K, M ⋆ = 1.10M ⊙ , M H /M ⋆ = 1.02 × 10 −7 , M He /M ⋆ = 3.0 × 10 −4 , M cr /M ⋆ = 0.81, with a central 20 Ne abundance of 0.52.…”
Section: Sdss J08402123+5222174mentioning
confidence: 85%
“…The location of ultra-massive DA WD stars (Kleinman et al 2013;Kepler et al 2016;Curd et al 2017) are indicated with black star symbols. The black circles indicate the location of the known ultra-massive ZZ Ceti stars: BPM 37093 (Nitta et al 2016), SDSS J084021 (Curd et al 2017), GD 518 (Hermes et al 2013), and WD J212402 (Rowan et al 2019). up to date on the basis of the new grid of ONe-core WD models presented in Camisassa et al (2019) Rowan et al 2019). The location of these stars in the spectroscopic Hertzsprung-Russell (HR) diagram is shown in Fig.…”
Section: Introductionmentioning
confidence: 99%